2007
DOI: 10.1007/s11244-007-0275-y
|View full text |Cite
|
Sign up to set email alerts
|

H2 adsorption and H/D exchange on Au/TS-1 and Au/S-1 catalysts

Abstract: We report a combined quantum-mechanics/molecular-mechanics (QM/MM) analysis of H 2 dissociation and hydrogendeuterium (H/D) exchange on four potential active sites inside the TS-1 pores: (1) Au 3 /T6-Ti-non-defect, (2) Au 3 /T6-Si-non-defect, (3) Au 3 /T6-Ti-defect, and (4) Au 3 /T6-Si-defect. We provide full kinetic and thermodynamic data calculated at standard conditions (298.15 K, 1 atm) for Eley-Rideal mechanisms on these sites. The H/D exchange on Au 3 /TS-1 occurs in two steps: (1) first H 2 dissociation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 92 publications
3
13
0
Order By: Relevance
“…2 As for the case of 2 synthesized with NH 3 , a shift of the NH 2 bending modes could not be observed since d(ND 2 ) are expected to appear at 1131 and 1110 cm -1 which is an opaque region of silica. The appearance of a band at 2760 cm -1 is similar to the one described above and corresponds to the formation of Si-OD by H/D exchange with residual isolated silanols [24]. The IR spectrum of the deuterated amido imido complex thus obtained is equivalent to the spectrum of 2-d obtained by H/D exchange with D 2 (see Fig.…”
Section: In Situ Infrared Spectroscopysupporting
confidence: 67%
See 3 more Smart Citations
“…2 As for the case of 2 synthesized with NH 3 , a shift of the NH 2 bending modes could not be observed since d(ND 2 ) are expected to appear at 1131 and 1110 cm -1 which is an opaque region of silica. The appearance of a band at 2760 cm -1 is similar to the one described above and corresponds to the formation of Si-OD by H/D exchange with residual isolated silanols [24]. The IR spectrum of the deuterated amido imido complex thus obtained is equivalent to the spectrum of 2-d obtained by H/D exchange with D 2 (see Fig.…”
Section: In Situ Infrared Spectroscopysupporting
confidence: 67%
“…A broad and weak band raises the baseline at 3200 cm -1 . This effect and the shift of the silanol stretching frequency are explained by the interaction of ammonia with the silanols of silica via van der Waals interactions [24], and was confirmed by blank experiments.…”
Section: In Situ Infrared Spectroscopysupporting
confidence: 60%
See 2 more Smart Citations
“…In their studies, both metadynamics and constrained molecular dynamics (MD) simulations highlight important fluctuations of the Au cluster during the reaction process, which is consistent with the geometric fluxionality of Au particles aforementioned [69]. Later, Thomson et al compared the catalytic activity of Au3, Au 4 + , Au5, and Au 5  clusters in the gas-phase reaction of H2 and O2 to form H2O2 [85]. It was found that both neutral and charged Au clusters are active in the peroxide formation reaction, but Au 4 + is the most active one for H2O2 formation based on the Gibbs free energy of activation.…”
Section: The Synthesis Of H 2 O 2 From O 2 and Hmentioning
confidence: 82%